Menilik Dampak Kebijakan Peningkatan PPN 11% Pada Masyarakat Indonesia Sesuai UU No. 7 Tahun 2021 tentang Harmonisasi Peraturan Perpajakan - Nabila Septia Rosa (Faculty of Social and Political Science, 2024)
One of the important fiscal instruments for Indonesia's state revenue is taxes, which are used to achieve development targets. The decline in social activity due to the pandemic has impacted income tax receipts, potentially weakening the country's taxation sector and overall economic growth. Government regulations refer to unstable economic conditions so that new policies have been realized and passed in accordance with UU No.7 Tahun 2021 tentang kenaikan pajak pertambahan nilai (PPN) menjadi 11 %. The purpose of this study is to determine the impact of the 11% PPN increase policy which took effect on April 1, 2022 for the people of Indonesia. This research uses a qualitative method of literature study, using secondary data sources obtained from books, supporting articles, scientific papers, previous studies and other literature. The increase in PPN rates has an impact on all levels of society, especially those in the lower middle class because PPN is applied objectively, regardless of the status or income of the tax object. But in reality, this policy has a positive effect on Indonesia's economic growth followed by an increase in public consumption, so that tax revenue is able to make a significant contribution to state revenue.